Validation and reliability of a sources of knowledge scale for Brazilian coaches - José Carlos Mendes; Ricardo Brandt; Humberto Moreira Carvalho; Sebastián Feu; Sergio Jose Ibañez; Juarez Vieira Nascimento (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: The present study examined the validity of the Coaches' Training Profile Questionnaire (QPFT) in Brazilian coaches. Method: The questionnaire was back-translated and content validation was performed by an expert panel. Construct validation was based on the application of the questionnaire to 212 coaches from the state of Paraná, considering the Cronbach's alpha to examine internal consistency, Pearson's correlation and intraclass correlation coefficient (ICC) for test-retest reliability, and exploratory and confirmatory factor analysis. Results: The questionnaire showed high internal consistency, with Cronbach's alpha coefficient higher than .80. Correlations of the dimensions and ICC of the items indicated high reliability for the three dimensions of the questionnaire. The results of exploratory factor analysis explained a variance of 69.75%, with the AE factor explaining the largest portion of variance (27.01%) and the AT factor explaining the lowest portion of variance (21.14%). The absolute, parsimonious and incremental fit indices [X2 and p-value; X2/df; CFI, PCFI, GFI, PGFI, TLI, RMSEA (with 90% CI), and MECVI] were high. Conclusion: The Brazilian version of the QPFT presents a reliable and valid factor structure to identify coaches' knowledge sources in Brazil.